INFLUENCE OF SERVANT LEADERSHIP AND PSYCHOLOGY CAPITAL TO EMPLOYEES PERFORMANCE BY AS OF MEDIATION ORGANIZATION CITIZENSHIP BEHAVIOR (OCB) (Studies in District Education OfficeRembang) - HadiSubena, 13.5202.0022; Tjahjaningsih, Endang (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to analyze the effect of servant leadership and psychological capital to performance by as of mediation OCB studiesat theDistrict Education office Rembang. The population inthis studyisa civil servantat the District Education Office Rembang as many as128people, using the